2014
DOI: 10.1111/ajps.12088
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Theory of Budgetary Politics and Some Empirical Tests: The U.S. National Budget, 1791–2010

Abstract: We develop a general theory of budgetary politics and examine its implications on a new data set on U.S. government expenditures from 1791 to 2010. We draw on three major approaches to budgeting: decision-making theories, primarily incrementalism and serial processing; policy process models; and path dependency. We show that the incrementalist budget model is recursive and that its solution is exponential growth, and isolate three periods in which it operates in pure form. The equilibrium periods are separated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 23 publications
1
19
0
2
Order By: Relevance
“…Moreover, in the case of budgets, issues that enjoy a high agenda position are also likely to occupy significant portions of the overall distribution of dollars within a budget. Similar to the findings of Jones, Zalányi, and Érdi (), even incremental changes can be large in real terms if the base is large, too. Thus, incremental changes can be major victories.…”
Section: Interest Group Dynamics and Policy Volatilitysupporting
confidence: 83%
“…Moreover, in the case of budgets, issues that enjoy a high agenda position are also likely to occupy significant portions of the overall distribution of dollars within a budget. Similar to the findings of Jones, Zalányi, and Érdi (), even incremental changes can be large in real terms if the base is large, too. Thus, incremental changes can be major victories.…”
Section: Interest Group Dynamics and Policy Volatilitysupporting
confidence: 83%
“…A series of empirical studies confirmed punctuated equilibrium, this alternative to classic incrementalism, for a range of US and Western European jurisdictions (Breunig, 2006(Breunig, , 2011Breunig and Koski, 2006;Baumgartner et al, 2009;Breunig et al, 2009;Jones et al, 2014). These confirmatory results prompted the formulation of a 'general empirical law of public budgets' (Jones et al, 2009).…”
Section: Theory and Hypothesesmentioning
confidence: 85%
“…Accordingly, large-scale data collection and coding projects were started (see, e.g. Breunig et al, 2009;Jones et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…All the single effects from Figure 1 have been analyzed empirically as well as theoretically: the filtering of information, limited attention in the agenda-setting process, institutional friction, and the leptokurtic behavior of policy outcomes. On the other hand, especially some of the latest contributions in PET have focused on the macro level of the whole process of information processing rather than on decisive policy changes (Breunig & Koski, 2012;Jones, Sulkin, & Larsen, 2003;Jones et al, 2009;Jones, Zalányi, & Érdi, 2014).…”
Section: Stochastic Process Models and Petmentioning
confidence: 99%